Deciphering composition and function of the root microbiome of a legume plant. Issue 1 (December 2017) - Hartman, Kyle; van der Heijden, Marcel; Roussely-Provent, Valexia; Walser, Jean-Claude; Schlaeppi, Klaus
Abstract Background Diverse assemblages of microbes colonize plant roots and collectively function as a microbiome. Earlier work has characterized the root microbiomes of numerous plant species, but little information is available for legumes despite their key role in numerous ecosystems including agricultural systems. Legumes form a root nodule symbiosis with nitrogen-fixingRhizobia bacteria and thereby account for large, natural nitrogen inputs into soils. Here, we describe the root bacteria microbiome of the legumeTrifolium pratense combining culture-dependent and independent methods. For a functional understanding of individual microbiome members and their impact on plant growth, we began to inoculate root microbiome members alone or in combination toTrifolium roots. Results At a whole-root scale, Rhizobia bacteria accounted for 70% of the root microbiome. Other enriched members included bacteria from the generaPantoea, Sphingomonas, Novosphingobium, andPelomonas . We built a reference stock of 200 bacteria isolates, and we found that they corresponded to 20% of the abundant root microbiome members. We developed a microcosm system to conduct simplified microbiota inoculation experiments with plants. We observed that while an abundant root microbiome member reduced plant growth when inoculated alone, this negative effect was alleviated if thisFlavobacterium was co-inoculated with other root microbiome members. Conclusions TheTrifolium root microbiome was dominated by nutrient-providingRhizobia bacteria and enriched for bacteria from genera that may provide disease protection. First microbiota inoculation experiments indicated that individual community members can have plant growth compromising activities without being apparently pathogenic, and a more diverse root community can alleviate plant growth compromising activities of its individual members. A trait-based characterization of the reference stock bacteria will permit future microbiota manipulation experiments to decipher overall microbiome functioning and elucidate the biological mechanisms and interactions driving the observed effects. The presented reductionist experimental approach offers countless opportunities for future systematic and functional examinations of the plant root microbiome.